Rekomendasi Penentuan Target Pemasangan Iklan Facebook Ads Menggunakan Metode SAW - Anief Fauzan Rozi; Suryadin Suryadin (Faculty of Computer Science, University of Jember, 2019)
In determining the interest of potential customers on Facebook, so far there are no tools and basic benchmarks as indicators that can be used as a reference for them to determine the target of online advertising. There is also no tool found in the form of software in the form of a decision support system that can help business people to process data and make decisions. The purpose of this study was to create a decision support system software for determining Facebook ads using the SAW method, with 6 criteria, namely the preferred page, likes, comments, shared, redeemed ads, ads clicked. The results of calculations using the system as well as those that have been manually calculated indicate that recreation is the best interest because it is based on a value of 14.60, with a percentage of suitability of 100%. So that the designed system can be used as a decision-making tool.